English Learning Interest in High School Students: TPACK-Based Problem-Based Learning Model - Hamsia, Hamsia; Sunra, La; Iryani, Neni (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The motivation for this research stems from the students' dissatisfaction with their low learning scores, which range from 66.84 to 68% for 23 students. The English learning achievement test results remain unsatisfactory, with only 65% of the 23 students completing the minimum completion criteria (70) exam. Therefore, this study aims to describe the implementation of the TPACK approach through the problem-based learning (PBL) model, with the goal of improving learning interest and English learning outcomes. This is classroom action research conducted in two cycles. The sample for this study was 23 students of public Senior High School 1 Nosu in grade X. The study collected data on students' attitudes, interests, and sincerity in following the learning process through the TPACK-integrated Problem-Based Learning (PBL) Model. Data analysis uses qualitative and quantitative analysis techniques. The study's results indicated that in the first cycle, the percentage of students who completed the learning achievement test increased to 73.9%. Likewise, learning interest also increased to the good category, namely 78.25%. Furthermore, in cycle 2, learning interest increased again, to the good category of 91.3%. Similarly, the proportion of students who successfully completed their learning achieved a significant increase to 95.64%.